(untitled) (Health Renaissance, 2016)
Background: Various goals of premedication includes anxiolysis, sedation, amnesia, analgesia, attenuation of autonomic reflexes, and reduction of anaesthetic dose requirement. Preanaesthetic oral clonidine has been shown to produce anxiolysis, sedation and attenuation of hemodynamic stress response to tracheal intubation. Objective: To investigate the clinical efficacy of oral clonidine on propofol consumption in patients undergoing laparoscopic cholecystectomy. Methods: This was a prospective, randomized, double-blind placebo controlled study conducted in ninety consecutive patients randomly divided into three equal groups (placebo, tab. clonidine 150 mcg and tab. clonidine 300 mcg) meeting inclusion and exclusion criteria who underwent laparoscopic cholecystectomy. Study drug was given 60 minutes before induction of anaesthesia. Anaesthesia was induced with intravenous pethidine 1mg/kg followed by propofol . The dose of propofol for loss of verbal command was recorded. Anaesthesia was maintained with propofol at the rate of 10 mg/kg/h for 10 minutes then to 8 mg/kg/h for 10 minutes and ultimately decreased to 6 mg/kg/h after tracheal intubation. The rate of propofol infusion was adjusted by 2mg/kg/h to obtain adequate depth of anaesthesia (maintaining hemodynamic parameters within 20% of baseline). Results: The propofol induction dose was less in clonidine 150 mcg (1.2±0.2 mg/kg) and clonidine 300 mcg (1.08±0.24 mg/ kg) groups as compared to placebo group ( 1.4±0.3 mg/kg) (p=˂0.001). The rate of propofol infusion in mg/kg/h and in mcg/kg/h was lower in clonidine 150 mcg (6.7±1.6 and 121.3±11.37) and clonidine 300 mcg (7±1.4 and 120.0±9.8) groups as compared to placebo (10±3.2 and 148.0±32.53) group (p =˂ 0.001). Conclusion: oral clonidine premedication reduces propofol requirement for induction and maintenance of anaesthesiain patients undergoing laparoscopic cholecystectomy. Health Renaissance 2014;12(3): 204-208